Coordination of bilateral tooth replacement in the juvenile gecko is continuous with in ovo patterning. Issue 2 (10th January 2018) - Grieco, Theresa M.; Richman, Joy M.
Abstract : We performed a test of how function impacts a genetically programmed process that continues into postnatal life. Using the dentition of the polyphyodont gecko as our model, tooth shedding was recorded longitudinally across the jaw. We compared two time periods: one in which teeth were patterned symmetrically in ovo and a later period when teeth were initiated post‐hatching. By pairing shedding events on the right and left sides, we found the patterns of tooth loss are symmetrical and stable between periods, with only subtle deviations. Contralateral tooth positions shed within 3–4 days of each other in most animals (7/10). A minority of animals (3/10) had systematic tooth position shifts between right and left sides, likely due to changes in functional tooth number. Our results suggest that in addition to reproducible organogenesis of individual teeth, there is also a neotenic retention of jaw‐wide dental patterning in reptiles. Finer analysis of regional asymmetries revealed changes to which contralateral position shed first, affecting up to one quarter of the jaw (10 tooth positions). Once established, these patterns were retained longitudinally. Taken together, the data support regional and global mechanisms of coordinating tooth cycling post‐hatching.